The effect of production systems on beef fatty acid composition - Mojca VOLJČ; Alenka LEVART; Marko ČEPON; Silvester ŽGUR (Acta Agriculturae Slovenica)
The aim of the present study was to evaluate the effect of different production systems on fatty acids (FA) composition of three beef muscles (longissimus thoracis, semitendinosus and diaphragmae). The first group (MGSC) included 8 bulls of Slovenian Brown breed that were fattened with maize, grass silage and concentrates. The second group (MCS) included 8 bulls of Slovenian Simental breed that were fattened with maize silage, ensiled corn grain and concentrates. The third group (GS) included 6 Limousine × Simmental crossbreed bulls that have been fattened on pasture in cow-calf production system until slaughter. In fourth group (G) 8 bulls of Slovenian Simmental breed were fattened on pasture from spring to autumn when they were slaughtered. Bulls from MSC and MGSC had similar carcass weight (316 kg, 308 kg, respectively), whereas bulls from GS had the lightest (215 kg) and bulls from G the heaviest carcass weight (371 kg). Carcass fatness was similar for bulls in MSC, MGSC and G groups and slightly lower in GS group. The percentage of saturated FA differed among groups only in semitendinosus muscle. Bulls from G and GS had lower percentage of monounsaturated FA (MUFA) and higher percentage of polyunsaturated FA (PUFA) in all three muscles. Bulls from grazing production systems had higher n-3 PUFA values in all muscles and higher n-6 PUFA values in semitendinosus and diaphragmae. Bulls fattened on pasture had lower n-6/n-3 ratio in all three muscles. Bulls from GS had a higher percentage of conjugated linolenic acid in comparison to MGSC and MCS groups in all muscles except in semitendinosus where percentage of CLA was higher only from MGSC group.